Complexing Agents on Carbon Content and Lithium Storage Capacity of LiFePO4/C Cathode Synthesized via Sol-Gel Approach - C. Guan; H. Huang (Advances in Materials Science and Engineering)
Olivine-structured LiFePO4 faces its intrinsic challenges in terms of poor electrical conductivity and lithium-ion diffusion capability for application to lithium-ion batteries. Cost-effective sol-gel approach is advantageous to in situ synthesize carbon-coated LiFePO4 (LiFePO4/C) which can not only improve electronic conductivity but also constrain particle size to nanometer scale. In this study, the key parameter is focused on the choice and amount of chelating agents in this synthesis route. It was found that stability of complexing compounds has significant impacts on the carbon contents and electrochemical properties of the products. At the favorable choice of precursors, composition, and synthesis conditions, nanocrystalline LiFePO4/C materials with appropriate amount of carbon coating were successfully obtained. A reversible capacity of 162 mAh/g was achieved at 0.2C rate, in addition to good discharge rate capability.